A Comparative Analysis On Methods For Measuring Web Usability - Rohana, Husin (2004)
There are many methods in measuring web usability. Each method has its strenght and limitation. This study identified the top three most commonly-used methods in measuring web usability. The three methods were applied and tested using a prototype designed with some major flaws. The results show that usability testing, heuristic evaluation, and cognitive walkthrough are the top three methods, and usability testing method (think-aloud technique) is more preferable than the other two in terms of usability problem identified and cost effectiveness.